Hydraulic binder for mortar composition and preparation method thereof
By using a gelling system composed of overfired magnesium oxide, soluble phosphate and retarder in ceramic tile adhesive, combining mineral blends and graded sand, and using polyacrylamide and water-absorbing resin as thickeners, the problems of long hardening time and slow bonding strength of existing ceramic tile adhesives are solved, and the effects of fast hardening and early strength and good volume stability are achieved.
Patent Information
- Application Number
- CN202411838014.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
During construction, existing ceramic tile adhesives have quality problems such as excessive hardening time, slow bonding strength development, strict maintenance conditions, and may cause hollowing and falling off of tiles in the later stage.
A gelling system consisting of perfired magnesium oxide, soluble phosphate and suitable retarder is adopted, combined with mineral blends and graded sand, polyacrylamide and water-absorbing resin are used as thickeners, and the coagulation hardening speed and bonding strength of the magnesium phosphate gelling system are improved through the dual role of the retarder and inorganic temperature regulator.
It realizes the fast hardness and early strength of ceramic tile adhesives, shortens the construction period, improves the bonding strength and volume stability, reduces the risk of later shrinkage and cracking, and ensures the safety and durability of ceramic tiles.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a hydraulic binder for a mortar composition and a preparation method thereof. Background Art
[0002] With the rapid development of my country's economy and urbanization in the past decade, the real estate industry has increased greatly, and building materials that meet different needs have emerged in an endless stream. Whether it is the construction of new houses or the renovation of old houses, ceramic tile products are increasingly used in the construction industry, and the types and usage scenarios of ceramic tiles are gradually improving. The "2022 China Ceramic Tile (Wave) Capacity Survey Report" shows that the national ceramic tile production capacity has increased from 12.32 billion square meters in 2020 to 12.56 billion square meters in 2022, with a growth rate of 1.91%. However, in 2022, due to factors such as weakening demand, rising energy and raw material prices, environmental protection supervision and the impact of real estate thunder, the national ceramic tile output was 7.31 billion square meters, a year-on-year decrease of 12.74%. According to data from the World Ceramic Tile Forum, during the statistical period from 2006 to 2021, China's ceramic tile production accounted for more than 50% of the global total production. It can be seen that despite the decline in production, the total volume of my country's ceramic tile market is still huge.
[0003] As one of the types of ceramic tiles with a relatively large proportion, vitrified tiles have become the mainstream tiles in the construction industry in recent years and have become the mainstream trend of the current ceramic tile market. In the early days, workers mainly used cement and fine sand to mix and paste ceramic tiles. This method has a certain effect on the pasting of ceramic tiles with rough surfaces and high water absorption, but it is difficult to form an effective paste for vitrified tiles with denser surfaces and extremely low water absorption, and the later pasting effect is very poor. In recent years, there are many types of tile adhesive products specifically used for pasting ceramic tiles, and some products need to be used with backing glue. However, the quality of ceramic tiles and backing glue products on the market varies, the construction level of workers is different, and the on-site construction environment is relatively complex. Therefore, when the performance of the tile adhesive is poor, or when the tile adhesive is not sufficiently considered in the design of the tile adhesive, after the tile adhesive is pasted on the wall, it is affected by various complex service environments. As the age increases, the tiles often have hollow drums and fall off in the later period.
[0004] In recent years, the production of ceramic tile adhesives at home and abroad is complete and varied, mainly including cement-based adhesives, epoxy adhesives, emulsion-based adhesives, highly flexible adhesives, water-dispersible adhesives, water-dispersible polymer cement mortars, solvent-based adhesives and reactive adhesives. At present, the mainstream products of ceramic tile adhesives in my country are mainly cement-based adhesives, among which the most common and mainstream is ordinary silicate cement-based ceramic tile adhesives. The ceramic tile adhesives prepared with dispersible latex powder and water-retaining agent have the advantages of stable quality, high bonding strength and good durability. However, the early strength growth of silicate cement-based ceramic tile adhesives is slow, and the maintenance temperature and humidity are harsh. In the later stage of pasting ceramic tiles, shrinkage behaviors such as shrinkage and chemical shrinkage may cause cracks inside the ceramic tile adhesive, reduce the bonding ability of the ceramic tile adhesive, and reduce the reliability of bonding with ceramic tiles. In severe cases, quality problems such as hollowing and falling of ceramic tiles may occur. At the same time, due to the slow development of strength of silicate cement-based tile adhesive, in order to shorten the construction period and save management and construction costs, many construction units will carry out multiple types of work simultaneously and interspersed. In order to protect the existing construction work, the construction site needs to protect the finished product. If the tile adhesive has the characteristics of fast hardening and early strength, and the early strength develops rapidly, it will greatly shorten the construction period, reduce the difficulty of cross-operation, and may also save the finished product protection after tiling to ensure the safe laying effect of tiles, thereby further reducing construction costs.
[0005] In recent years, domestic universities and enterprise researchers have also started the research and development of fast-hardening and early-strengthening ceramic cement-based tile adhesives in response to the problem that ordinary silicate cement-based tile adhesives take a long time to harden and are not suitable for rapid construction. The first thing that comes to mind is to add inorganic salt early-strengthening agents, such as calcium formate, calcium chloride, lithium carbonate, etc., or organic early-strengthening agents such as triethanolamine and triisopropanolamine, etc., to the silicate system. Although such early-strengthening agents can effectively shorten the cement hydration time and make the strength of the cementitious system develop rapidly, it still takes more than ten hours or even dozens of hours for the tile adhesive to reach final setting. Moreover, the dosage of such early-strengthening agents is more sensitive to the stability of cement-based tile adhesive products. If the dosage is too large, the tile adhesive may shrink more in the later stage and the strength may shrink. When the dosage of some early-strengthening agents is large, they even show slow setting in the system, which seriously affects the performance of ordinary silicate cement-based tile adhesive products.
[0006] In addition, the rapid hardening and early strengthening effect of cement-based tile adhesive can also be achieved by adding gypsum, high-aluminum cement, etc. to ordinary silicate cement to form a binary or ternary cementitious system. The interaction between ordinary silicate cement and / or high-aluminum cement and gypsum binary or ternary systems will generate a large amount of calcium sulfonate, which will promote the rapid hardening of the adhesive. At the same time, the formation of calcium sulfonate is conducive to filling the gaps between the mortar, making the adhesive denser and stronger. Although this system can achieve the purpose of rapid hardening and early strength, the raw materials in this system, especially the high-aluminum cement products, fluctuate greatly, and the storage requirements are high. At the same time, the quality control requirements for production equipment, production and transportation processes are high. The quality stability of tile adhesive products is not good, and there are hidden dangers in the safe laying of tiles in the later stage.
[0007] A Chinese patent with publication number CN105503106A discloses a fast-hardening high-strength tile adhesive. The formula uses 2 to 10 parts of anhydrous gypsum or semi-hydrated gypsum, 0.2 to 2.5 parts of an early strength agent, and 0.05 to 0.2 parts of a retarder. The tile adhesive is prepared with ordinary Portland cement or high-alumina cement, mineral admixtures, quartz sand, anti-cracking wood fiber and admixtures. The tile adhesive has the advantages of high bonding strength, long operating time, and fast hardening speed. The bonding strength of the prepared adhesive meets the requirements of industry regulations within 24 hours. The high-strength adhesive increases the construction speed and accelerates the construction progress.
[0008] A Chinese patent with publication number CN108675734A discloses a high-performance fast-hardening tile adhesive, which is composed of the following components in parts by weight: 30-40 parts of cement, 8-10 parts of gypsum, 50-65 parts of quartz sand, 2-3 parts of redispersible latex powder, 0.2-0.3 parts of water retaining agent, 0.15-0.3 parts of early strength agent and 0.04-0.09 parts of retarder. The adhesive has the characteristics of fast hardening and high strength, can quickly coagulate and harden, and the tensile adhesion strength in 6 hours can meet the industry standard requirement of 0.5MPa. The operating time is not less than 40 minutes, which has sufficient operating time and is also green and environmentally friendly.
[0009] Although for the system composed of ordinary Portland cement, high-alumina cement and gypsum, the strength of cement-based tile adhesive develops rapidly after reasonable proportion and sufficient mixing, which can achieve the advantages of fast construction and shortened construction period. However, the fluctuation of raw materials, insufficient mixing and unreasonable proportion may lead to the cement hydration developing too slowly and insufficient strength, or the cement hydration is too fast and the material cannot be constructed, which may also lead to the decline of strength in the later stage. Only when the three materials are relatively stable, through sufficient mixing and reasonable proportion, can the speed of strength development and the shrinkage rate of the materials be controlled. Therefore, although such a system can achieve the purpose of fast hardening and early strength, it has certain challenges to the stability of raw materials, production stability, quality control and normal construction.
[0010] In recent years, there have been many studies on magnesium phosphate cement. Magnesium phosphate cement is a kind of environmentally friendly cementitious material, which is made of magnesium oxide and soluble phosphates mixed in a certain proportion. Magnesium oxide is obtained by grinding magnesite after high-temperature calcination. Soluble phosphates are mainly ammonium dihydrogen phosphate (NH4H2PO4) and potassium dihydrogen phosphate (KH2PO4). Taking KH2PO4 as an example, it reacts with magnesium oxide to form potassium magnesium phosphate cement (MKPC for short). The main hydration product is struvite (MgKPO4·6H2O, MKP for short). The crystal structure of MKP is mainly composed of PO3-4 tetrahedron, MgO·6H2O octahedron and K + The research results of Ding Zhu et al. [Ding Zhu, Li Zongjin. Preparation and properties of early strength phospho-silicate cement [J]. Journal of Materials Research, 2006, (2): 141-147] show that the main hydration product of MKPC is MKP, and the main equation is MgO+KH2PO4+5H2O=MgKPO4·6H2O. In addition, some studies have found that the hydration product MKP of MKPC is mainly short rod-shaped. Figure 1 As shown, Figure 1 The middle left picture shows the crystal structure of MKP, and the right picture shows the SEM morphology of MKP.
[0011] Compared with traditional cement, magnesium phosphate cement is simple and convenient to operate. It reacts quickly and releases a lot of heat after mixing with water. Under normal conditions, a rapid reaction occurs within a few minutes. The products after the reaction are cemented, and the unreacted magnesium oxide forms a material structure with other fillers. Compared with ordinary silicate cement, it has the advantages of fast setting and hardening speed, high early strength, high bonding strength, small drying shrinkage, construction under low temperature environment, high wear resistance and antifreeze performance. The chemical reaction produces a highly crystalline material with excellent characteristics of ceramic products, so it is also called "chemically bonded magnesium phosphate ceramics."
[0012] However, magnesium phosphate cement will also encounter some thorny problems in the specific construction and application process: due to its fast setting time, it sets and hardens in a few minutes, and the construction operability is poor. In addition, it has a large heat release, fast early strength development, and is accompanied by temperature crack morphology. In recent years, magnesium phosphate cement has been widely studied in grouting repair materials. It has the characteristics of convenient construction, fast hardening, high early strength, micro expansion, strong adhesion with the substrate and good compatibility. It has more advantages than cement-based grouting repair materials prepared by silicate cement and sulphoaluminate cement. However, magnesium phosphate cement-based grouting repair materials have the defects of setting too fast and large fluidity loss at room temperature or high temperature, which limits its application range; and the early and late strength of this type of grouting repair material after excessive slow setting cannot meet the requirements of ultra-early strength and ultra-high strength, and cannot meet the repair requirements of high-strength concrete. In order to solve many problems, people continue to study the modification of magnesium phosphate cement.
[0013] A Chinese patent with publication number CN103922694A discloses a magnesium phosphate cement-based composite material. By adding silicate cement and sulphoaluminate cement to magnesium phosphate cement, the setting time of the magnesium phosphate cement-based composite material is increased and the water resistance is also improved to a certain extent. At the same time, the cement has the advantages of appropriately extending the setting time and improving the water resistance while maintaining the strength of the magnesium phosphate cement, low cost, flexible application, etc., and has good promotion and application.
[0014] The Chinese patent with publication number CN102643073A discloses a magnesium phosphate cement grouting material, which uses borax as a setting regulator. The invented grouting material has good volume stability, fast early hardening and high strength, can be hydrated at negative temperatures, has good corrosion resistance, and is easy to construct. However, due to the limited retarding effect of borax, the grouting material hydration reaction speed is too fast, the fluidity loss is large, and there is not enough construction time at normal ambient temperature, so the scope of application is limited.
[0015] The Chinese patent with publication number CN108069692A discloses a magnesium phosphate grouting material for rapid repair and a preparation method thereof, wherein the magnesium phosphate grouting material for rapid repair uses boric acid as a retarder, and the setting time is moderately controllable. However, due to the large amount of boric acid added, the hydration activity of the acid and alkali components is inhibited, resulting in low early flexural and compressive strengths (1d, 5.3-8.2MPa, 37.1-51.1MPa), and limited later strength development, which cannot meet the engineering requirements of ultra-early strength and ultra-high strength.
[0016] A Chinese patent with publication number CN105330197A discloses a magnesium phosphate cement-based composite material performance regulating admixture, which uses chloride salt as a setting regulating component. Although it solves the disadvantage of too fast early strength development of concrete and cracks, in reinforced concrete structures, the addition of a large amount of chlorine will corrode the steel bars, causing performance degradation and changes in the internal structure; increasing the water-cement ratio and increasing the amount of retarder can effectively improve its construction performance, but it will significantly reduce the strength of magnesium phosphate cement, thereby reducing the strength of cement concrete.
[0017] A Chinese patent with publication number CN114956773A discloses a fast-hardening and early-strengthening ultra-high performance magnesium phosphate cement-based material, which is made of dead-burned magnesium oxide, basic hydrogen phosphate, silica fume, ultrafine mineral admixture, steel fiber, sand and water as raw materials. It can solve the problems of cumbersome maintenance, slow strength development, difficult on-site construction, difficult reinforcement and repair of materials in existing ultra-high performance concrete, and low mechanical properties of magnesium phosphate cement fiber reinforced materials, which cannot meet the mechanical property requirements of ultra-high performance concrete and have a limited application range. It has ultra-high strength (28d strength can reach up to 212MPa), simple maintenance (air curing), fast hardening and early strength (1d strength can reach more than 70MPa), which provides convenience for on-site construction and emergency repair of materials, and expands the application range of magnesium phosphate cement. It has good economic and environmental benefits and is suitable for large-scale promotion and application, but also has the problem of short setting time.
[0018] In summary, the main problem of magnesium phosphate cement is its short setting time. Currently, the main retarder is borax or boric acid, but borax has little effect on extending the setting time of magnesium phosphate cement. Only when a large amount of borax is added can the setting time be extended to a large extent, and in this case, the strength of magnesium phosphate cement decreases significantly, and borax or boric acid is very harmful to the human body, and improper use may damage human health.
[0019] And although there are many studies on magnesium phosphate cement in terms of raw material selection and quality control, there is still room for further improvement. The research on magnesium phosphate cement is still immature. Magnesium phosphate cement has a short setting time and is not suitable for large-volume repairs, resulting in almost no application of magnesium phosphate cement in tile adhesives.
[0020] In addition, with the continuous development of ceramic tiles in the building decoration industry, most of the walls and floors of public places such as venues, hotels, and scenic spots are paved with ceramic tiles. However, in recent years, the tiles on the walls and floors of such places have fallen off and broken from time to time, which not only has a great impact on the beauty of the place, but also poses a huge safety hazard to pedestrians. For site managers, the best way is to restore the original appearance as soon as possible and quickly paste the tiles safely and reliably so as not to affect the subsequent use effect. At present, the most common repair method is to use epoxy resin adhesives for rapid repair. Although epoxy resin adhesives have the advantages of rapid strength development, high bonding strength, good construction performance and low shrinkage in the later stage, they also have some disadvantages. For example, for the rapid recovery of outdoor tile pasting, its UV resistance is poor; for the rapid recovery of indoor tile pasting, it will continuously release harmful gases such as formaldehyde and VOC during the construction process and the later service process, which is harmful to the human body and not environmentally friendly. Moreover, epoxy resin adhesives are expensive and will greatly increase the construction cost.
[0021] Based on the above facts, it is necessary to invent an early-strengthening tile adhesive with cement as the main cementitious material, which has the characteristics of fast hardening and early strength, and is environmentally friendly and harmless to the human body, in order to shorten the construction period, reduce construction costs and quickly repair tile detachment. Summary of the invention
[0022] In view of this, the technical problem to be solved by the present invention is to provide a hydraulic binder for a mortar composition with fast hardening, early strength and simple maintenance and a preparation method thereof.
[0023] The present invention provides a mortar composition with a hydraulic binder, comprising:
[0024] 20-50 parts by weight of overburned magnesium oxide;
[0025] 8 to 30 parts by weight of soluble phosphate;
[0026] 5 to 19 parts by weight of mineral admixture;
[0027] 25-60 parts by weight of graded sand;
[0028] 0 to 9 parts by weight of redispersible latex powder;
[0029] 0.05-0.5 parts by weight of inorganic temperature regulator;
[0030] Thickener 0.1-3 parts by weight;
[0031] Surfactant 0-0.1 parts by weight;
[0032] 0.1 to 0.5 parts by weight of thixotropic lubricant;
[0033] Retarder; the mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition;
[0034] The thickener is selected from polyacrylamide and water-absorbing resin.
[0035] Preferably, the mass ratio of the polyacrylamide to the water-absorbing resin is 0.2-1:1-4.
[0036] Preferably, the mineral admixture comprises 5 to 12 parts by weight of heavy calcium powder and 0 to 7 parts by weight of ultrafine filler.
[0037] Preferably, the fineness of the heavy calcium powder is 200-400 mesh;
[0038] The average particle size of the ultrafine filler is 0.2 to 20 μm;
[0039] The ultrafine filler is selected from one or more of silica fume, metakaolin, granulated blast furnace slag powder, fly ash, limestone powder and heavy calcium powder.
[0040] Preferably, the graded sand includes 40-70 mesh sand and 70-140 mesh sand;
[0041] The mass ratio of the 40-70 mesh sand to the 70-140 mesh sand is (0.7-1.2):1.
[0042] Preferably, the overburned magnesium oxide is obtained by calcining and grinding magnesite at a high temperature of 1500°C to 1700°C;
[0043] The overburned magnesium oxide has a mesh size of 250 to 400;
[0044] The MgO content in the overburned magnesium oxide is 88% to 92%;
[0045] The soluble phosphate is selected from one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, calcium hydrogen phosphate, disodium hydrogen phosphate and sodium dihydrogen phosphate;
[0046] The graded sand is selected from one or more of washed sand, machine-made sand, quartz sand and calcium sand;
[0047] The redispersible latex powder is selected from one or more of vinyl acetate-ethylene copolymer, vinyl acetate-ethylene-vinyl versatate polymer, styrene-acrylate copolymer, vinyl acetate-vinyl versatate-acrylic acid-ethylene copolymer and vinyl chloride-ethylene-vinyl laurate copolymer;
[0048] The inorganic temperature regulator is selected from one or more of ammonium nitrate, potassium nitrate and ammonium chloride;
[0049] The surfactant is selected from acetylenic glycol surfactants;
[0050] The thixotropic lubricant is selected from one or more of inorganic bentonite, attapulgite, and sepiolite;
[0051] The retarder is selected from one or more of citrate, benzoate, tartrate, bromate, iodate, acetate and formates.
[0052] Preferably, the hydraulic binder of the mortar composition further includes water; the mass of the water is 10% to 20% of the total mass of other components of the hydraulic binder of the mortar composition except water.
[0053] Preferably, it includes:
[0054]
[0055] 0.03-0.07 parts by weight of surfactant;
[0056] Thixotropic lubricant 0.1-0.3 parts by weight;
[0057] Retarder; the mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition.
[0058] Preferably, including:
[0059] 25-30 parts by weight of overburned magnesium oxide;
[0060] 8.5-10 parts by weight of soluble phosphate;
[0061] 11.5-15 parts by weight of mineral admixture;
[0062] 40-50 parts by weight of graded sand;
[0063] Redispersible latex powder 0-0.5 parts by weight;
[0064] 0.2 parts by weight of inorganic temperature regulator;
[0065] Thickener 0.18-0.44 parts by weight;
[0066] 0.03-0.07 parts by weight of surfactant;
[0067] 0.2-0.3 parts by weight of thixotropic lubricant;
[0068] Retarder; the mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition.
[0069] The present invention also provides a method for preparing the above-mentioned mortar composition using a hydraulic binder, comprising the following steps:
[0070] The overburned magnesium oxide, soluble phosphate, mineral admixture, graded sand, redispersible latex powder, inorganic temperature regulator, thickener, surfactant, thixotropic lubricant and retarder are mixed to obtain a hydraulic binder for a mortar composition.
[0071] The invention provides a hydraulic binder for a mortar composition, comprising: 20 to 50 parts by weight of overburned magnesium oxide; 8 to 30 parts by weight of soluble phosphate; 5 to 19 parts by weight of mineral admixture; 25 to 60 parts by weight of graded sand; 0 to 9 parts by weight of redispersible latex powder; 0.05 to 0.5 parts by weight of an inorganic temperature regulator; 0.1 to 3 parts by weight of a thickener; 0 to 0.1 parts by weight of a surfactant; 0.1 to 0.5 parts by weight of a thixotropic lubricant; and a retarder; the mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder for the mortar composition; and the thickener is selected from polyacrylamide and a water-absorbing resin. Compared with the prior art, the present invention uses a gelling system prepared by overburned magnesium oxide, soluble phosphate and a suitable retarder, and adds a tile adhesive mortar prepared by conventional materials, which has extremely low water demand and good construction performance; and the present invention adopts the dual effects of a retarder and an inorganic temperature regulator, thereby improving the technical problem that the magnesium phosphate gelling system coagulates and hardens too quickly, and the tile adhesive is difficult to construct; polyacrylamide and a water-absorbing resin are also used as thickeners to solve the problem that conventional cellulose ether water-retaining agents fail to retain water in the magnesium phosphate gelling system, thereby making the tile adhesive open for a long time, having the characteristics of fast hardening and early strength, greatly shortening the curing age after pasting tiles, thereby greatly shortening the construction period, and being able to provide a subsequent construction work surface as soon as possible, providing more sufficient construction time for subsequent construction operations; at the same time, the adhesive is made dense inside, the hydration product is water-resistant and high-temperature-resistant, can cope with various complex service environments, and has a high safety factor for bonding tiles; and the magnesium phosphate gelling system has basically no volume shrinkage and expansion over a long period of time, has good volume stability, and the adhesive hardened body will not shrink and crack during service, thereby improving the safety of tile paving in the later stage.
[0072] The experimental results show that the tensile bonding strength of the mortar composition prepared by the present invention can reach 0.6MPa under a standard environment of 6h using a hydraulic binder, which can greatly shorten the curing time after the tile is paved, save the construction age, and effectively reduce the construction and management costs, all of which have significant economic benefits; the mortar composition prepared by the present invention has very low shrinkage using a hydraulic binder, and the shrinkage rate does not exceed 0.1% under a standard curing environment of 28d, and its volume stability is excellent, and the tile is firmly and reliably pasted with good durability; the mortar composition prepared by the present invention uses a hydraulic binder through reasonable formula optimization, and inorganic and organic additives such as retarders and temperature regulators and raw materials such as overburned magnesium oxide work synergistically, the raw materials used are very little harmful to the human body, the prepared binder has a long setting time, which meets the actual construction requirements, and the tile adhesive can be operated for no less than 20min, which can provide sufficient construction time for construction personnel and reduce material waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 This is the morphology of MKP, the hydration product of MKPC;
[0074] Figure 2 This is a graph showing the setting time test results of the mortar composition obtained in Examples 1 to 3 of the present invention using a hydraulic binder;
[0075] Figure 3 This is a temperature change diagram of the early system of the mortar composition using the hydraulic binder in Example 4 of the present invention and Comparative Examples 1 to 4;
[0076] Figure 4 This is a graph showing the setting time of the mortar composition using the hydraulic binder in Example 4 and Comparative Examples 1 to 4 of the present invention;
[0077] Figure 5 This is a graph showing the early strength test of the mortar composition using a hydraulic binder in Example 4 of the present invention and Comparative Examples 1 to 4;
[0078] Figure 6 The wetted area of tiles on the concrete slab using the hydraulic binder of the mortar composition obtained in Examples 5 to 8 of the present invention and Comparative Examples 5 to 6 is shown in FIG.
[0079] Figure 7 This is a comparison chart of the water retention of the mortar composition obtained in Examples 5 and 7 of the present invention and Comparative Examples 5 to 6 using the hydraulic binder on the concrete slab;
[0080] Figure 8 This is a graph of the early tensile bond strength of the mortar compositions obtained in Example 9 of the present invention and Comparative Examples 7 to 8 using a hydraulic binder. DETAILED DESCRIPTION
[0081] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0082] The present invention provides a mortar composition with a hydraulic binder, comprising:
[0083] 20-50 parts by weight of overburned magnesium oxide;
[0084] 8 to 30 parts by weight of soluble phosphate;
[0085] 5 to 19 parts by weight of mineral admixture;
[0086] 25-60 parts by weight of graded sand;
[0087] 0 to 9 parts by weight of redispersible latex powder;
[0088] 0.05-0.5 parts by weight of inorganic temperature regulator;
[0089] Thickener 0.1-3 parts by weight;
[0090] Surfactant 0-0.1 parts by weight;
[0091] 0.1 to 0.5 parts by weight of thixotropic lubricant;
[0092] Retarder; the mass of the retarder is 2% to 7% of the mass of MgO and soluble phosphate in the hydraulic binder of the mortar composition;
[0093] The thickener is selected from polyacrylamide and water-absorbing resin.
[0094] The adhesive provided by the present invention uses soluble phosphate and overburned magnesium oxide as gelling components and is adjusted by a suitable retarder, so that its early strength develops rapidly, the maintenance is simple, the bonding strength is high, and the curing period after tile paving can be greatly reduced, shortening the construction period; at the same time, the adhesive is basically free of volume shrinkage in the later stage of preparation, and has good volume stability, the tile adhesive is not easy to crack due to shrinkage, and the tile laying safety is high; in addition, the dual effects of the retarder + the temperature regulator are adopted to improve the technical problem that the magnesium phosphate gelling system coagulates and hardens too quickly and the tile adhesive is difficult to construct, and at the same time, the polyacrylamide + water-absorbing resin thickening system is adopted to solve the problem that the conventional cellulose ether water-retaining agent fails to retain water in the magnesium phosphate gelling system.
[0095] According to the present invention, the content of the overburned magnesium oxide in the hydraulic binder of the mortar composition is preferably 20 to 45 parts by weight, more preferably 20 to 40 parts by weight, more preferably 25 to 35 parts by weight, and most preferably 25 to 30 parts by weight; the overburned magnesium oxide is preferably obtained by calcining and grinding magnesite at a high temperature of 1500°C to 1700°C; the fineness of the overburned magnesium oxide is preferably 250 to 400 meshes; the density of the overburned magnesium oxide is preferably 3 to 4 kg / m 3 , more preferably 3.2 to 3.6 kg / m 3 , and preferably 3.4 to 3.5 kg / m 3 , the most preferred is 3.41kg / m 3 After being overburned, magnesium oxide can effectively reduce alkalinity and hydration activity, preventing the situation where the construction is difficult due to excessive reaction and short setting time in the initial stage of mixing with water. When used together with a suitable type of retarder, the working time of the adhesive can be extended.
[0096] According to the present invention, the content of the soluble phosphate in the hydraulic binder used in the mortar composition is preferably 8 to 25 parts by weight, more preferably 8 to 20 parts by weight, further preferably 8 to 15 parts by weight, further preferably 8 to 12 parts by weight, and most preferably 8.5 to 10 parts by weight; the soluble phosphate is preferably one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, calcium hydrogen phosphate, disodium hydrogen phosphate and sodium dihydrogen phosphate.
[0097] According to the present invention, the content of the mineral admixture in the hydraulic binder of the mortar composition is preferably 8 to 19 parts by weight, more preferably 10 to 16 parts by weight, and more preferably 11.5 to 15 parts by weight; in the present invention, specifically, the mineral admixture preferably includes 5 to 10 parts by weight of heavy calcium powder and 0 to 9 parts by weight of superfine filler, that is, 5 to 19 parts by weight of the mineral admixture in the hydraulic binder of the mortar composition consists of 5 to 12 parts by weight of heavy calcium powder and 0 to 7 parts by weight of superfine filler; the content of the heavy calcium powder in the hydraulic binder of the mortar composition is preferably 8 to 12 parts by weight, more preferably 10 to 12 parts by weight; the fineness of the heavy calcium powder is preferably 200 to 400 mesh, more preferably 200-300 mesh, more preferably 250 mesh; the content of the ultrafine filler in the hydraulic binder of the mortar composition is preferably 1-7 parts by weight, more preferably 2-6 parts by weight, and more preferably 2.5-5 parts by weight; in some embodiments provided by the present invention, the content of the ultrafine filler in the hydraulic binder of the mortar composition is specifically 1.5 parts by weight, 2 parts by weight, 3 parts by weight or 4 parts by weight; the average particle size of the ultrafine filler is preferably 0.2-20 μm, more preferably 0.2-15 μm, more preferably 0.5-10 μm, more preferably 0.5-5 μm, and most preferably 0.5-2.5 μm; the specific surface area of the ultrafine filler is preferably 15000-20000 m 2 / kg, more preferably 16000 to 20000m 2 / kg, preferably 18000-19000m 2 / kg, the most preferred is 18500m 2 / kg; the ultrafine filler includes but is not limited to one or more of silica fume powder, metakaolin, granulated blast furnace slag powder, fly ash, limestone powder and heavy calcium powder; the ultrafine filler can optimize the particle grading of the binder powder, improve the flowability of the binder in the wet state, increase the density of the binder hardening system through physical filling and later participation in hydration, and improve the mechanical properties.
[0098] According to the present invention, the content of the graded sand in the hydraulic binder of the mortar composition is preferably 30 to 50 parts by weight, more preferably 35 to 50 parts by weight, more preferably 40 to 50 parts by weight, and most preferably 42 to 49 parts by weight; in some embodiments provided by the present invention, the content of the graded sand in the hydraulic binder of the mortar composition is specifically 45.7 parts by weight, 45.6 parts by weight, 48.8 parts by weight, 48.6 parts by weight or 42.5 parts by weight; the graded sand mainly refers to two or more continuous graded sands formed by screening and matching, including but not limited to washed sand, machine-made sand, quartz sand, calcium sand, etc., and the water content and mud content of the sand are required to meet the requirements of GB / T14684 "Construction Sand" standard. Sand is used as the aggregate of tile adhesive. Continuous grading can make the tile adhesive product form a dense stack, reduce the amount of fine powder, optimize the internal structure of the tile adhesive product, improve the workability, and improve the volume stability of the tile adhesive during drying. In the present invention, the graded sand preferably includes 40-70 mesh sand and 70-140 mesh sand; the mass ratio of the 40-70 mesh sand to the 70-140 mesh sand is preferably (0.7-1.2):1, more preferably (0.7-1.1):1, and even more preferably (0.75-1:1); in some embodiments provided by the present invention, the mass ratio of the 40-70 mesh sand to the 70-140 mesh sand is specifically 0.85:1, 0.88:1, 0.75:1 or 0.76:1.
[0099] According to the present invention, the content of the redispersible latex powder in the hydraulic binder of the mortar composition is preferably 0 to 9 parts by weight, more preferably 0 to 5 parts by weight, more preferably 0 to 3 parts by weight, more preferably 0 to 1 part by weight, and most preferably 0 to 0.5 parts by weight; the redispersible latex powder includes but is not limited to one or more of vinyl acetate-ethylene copolymer, vinyl acetate-ethylene copolymer, vinyl acetate-ethylene-versatate vinyl ester polymer, styrene-acrylate copolymer, vinyl acetate-versatate vinyl ester-acrylic acid-ethylene copolymer and vinyl chloride-ethylene-vinyl laurate copolymer. In the embodiments provided by the present invention, vinyl acetate-ethylene copolymer is specifically used as an example for explanation. The redispersible latex powder is an important organic gelling material in the binder, which directly affects the bonding strength and flexibility of the binder. After the binder is stirred with water, the latex powder will be redispersed into small emulsion particles evenly distributed in the wet mortar, and aggregated into a film at the interface between the binder and the tile, thereby improving the chemical bonding force between the tile, especially the low water absorption brick, and the binder. Although the hydration products of magnesium oxide and soluble phosphate in the formula react with water and have high bonding strength, the water requirement of the cementitious system is very low, and it is too dense after hardening and has a large elastic modulus. Therefore, a certain amount of redispersible latex powder needs to be added to the conventional formula to reduce the elastic modulus of the binder and increase the flexibility of the binder so as to better match the deformation problem between the base layer under extreme environments. However, the magnesium phosphate system used in the present invention has good bonding properties itself, and a good bonding effect can be achieved without the use of glue powder. Therefore, the content of redispersible latex powder in the hydraulic binder of the mortar composition provided by the present invention can be 0.
[0100] According to the present invention, the content of the inorganic temperature regulator in the hydraulic binder of the mortar composition is preferably 0.1-0.4 parts by weight, more preferably 0.1-0.3 parts by weight, and more preferably 0.2-0.3 parts by weight; the inorganic temperature regulator preferably includes but is not limited to one or more of ammonium nitrate, potassium nitrate and ammonium chloride. When the inorganic temperature regulator is added to the binder, on the one hand, the component can absorb a large amount of heat in the environment when it dissolves in water, which can offset the heat released when magnesium oxide and soluble phosphate react, causing a local low temperature environment or making the temperature in the reaction environment not rise much, thereby reducing the solubility of magnesium oxide and slowing down the reaction rate of magnesium oxide and soluble phosphate in the aqueous solution, and achieving the purpose of slow setting; on the other hand, the ammonium ions, potassium ions and other cations electrolyzed in the aqueous solution after the component dissolves in water are the same as the cations dissolved in the water by the soluble phosphate in the formula, thereby reducing the rate of ionization of the soluble phosphate to phosphate ions and cations, achieving the effect of reducing the concentration of reactive ions in the solution in the early stage of the reaction, thereby slowing down the reaction rate between magnesium oxide and soluble phosphate.
[0101] According to the present invention, the content of the thickener in the hydraulic binder of the mortar composition is preferably 0.1 to 2 parts by weight, more preferably 0.1 to 1 part by weight, and even more preferably 0.18 to 0.60 parts by weight; in some embodiments provided by the present invention, the content of the thickener in the hydraulic binder of the mortar composition is specifically 0.35 parts by weight, 0.24 parts by weight, 0.44 parts by weight, 0.2 parts by weight, 0.18 parts by weight or 0.25 parts by weight; the thickener is preferably polyacrylamide and water-absorbing resin; the molecular weight of the polyacrylamide Preferably, it is 5 to 20 million, more preferably 5 to 15 million, and even more preferably 8 to 10 million; the polyacrylamide can be any polyacrylamide known to those skilled in the art, and there is no special limitation. In the embodiments provided by the present invention, cationic polyacrylamide is specifically used as an example for illustration; the particle size of the water-absorbing resin is preferably 80 to 100 meshes; the water-absorbing resin is preferably a polymer water-absorbing resin, more preferably a spherical polymer water-absorbing resin, and even more preferably SAVIVAC300; in the embodiments provided by the present invention, BASF SAVIVAC300 polymer water-absorbing SAP super absorbent spherical polymer is used as an example for explanation; the mass ratio of the polyacrylamide to the water-absorbing resin is preferably 0.2-1:1-4; in some embodiments provided by the present invention, the mass ratio of the polyacrylamide to the water-absorbing resin is specifically 0.5:3, 0.4:2, 0.4:4, 1:1, 0.8:1 or 0.5:2; polyacrylamide and the water-absorbing resin are mixed in a certain proportion as a thickener, which can keep the surface and interior of the adhesive moist during the actual construction and air-drying process, and reduce the problem of loose adhesion to tiles caused by excessive drying due to surface water loss. The molecular chains of polyacrylamide and the water-absorbing resin are entangled with each other and overlapped with the particles of other components of the adhesive, which can effectively lock the moisture inside the adhesive, so that the adhesive can remain open for as long as possible, thereby improving the utilization rate of the adhesive. In addition, the construction process of the adhesive determines that the thickness of the mortar is mostly within 10mm. During the construction process, the adhesive scraped on the wall and the back of the tile may be exposed to the air for about 20 minutes. The addition of thickener can ensure that the tile glue will not be too dry during the 20 minutes exposed to the air, thereby ensuring that the tile is still wet mortar when it is pasted, ensuring the working time of the adhesive and the safety of the tile pasting.
[0102] According to the present invention, the content of the surfactant in the hydraulic binder of the mortar composition is preferably 0.01 to 0.08 parts by weight, more preferably 0.03 to 0.07 parts by weight; in some embodiments provided by the present invention, the content of the surfactant in the hydraulic binder of the mortar composition is specifically 0.06 parts by weight, 0.07 parts by weight or 0.03 parts by weight; the surfactant is preferably an acetylene glycol surfactant, more preferably an acetylene glycol nonionic surfactant. The surfactant is mainly composed of an acetylene glycol derivative (structure as shown in Formula I), and specifically relates to a water-dispersible dispersed powder composition of a polymer based on one or more ethylenically unsaturated monomers, wherein there are one or more dimerized surfactants, which can effectively improve the wetting properties of tile adhesives, optimize the internal void structure of the binder, and thus enhance the bonding strength of the binder. In the embodiments provided by the present invention, SURFYNOL 104E is specifically used as an example for illustration.
[0103]
[0104] According to the present invention, the content of the thixotropic lubricant in the hydraulic binder of the mortar composition is preferably 0.1 to 0.3 parts by weight, more preferably 0.2 to 0.3 parts by weight; the mesh size of the thixotropic lubricant is preferably 100 to 300 meshes, more preferably 100 to 200 meshes; the thixotropic lubricant preferably includes but is not limited to one or more of inorganic bentonite, attapulgite and sepiolite. The thixotropic lubricant can effectively improve the anti-slip property and wettability of the binder and improve the construction performance of the binder.
[0105] According to the present invention, the retarder is preferably 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition, and more preferably 3% to 6%; in some embodiments provided by the present invention, the retarder is specifically 5%, 3.75% or 6% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition; in the present invention, the retarder is one or more organic or inorganic salts, preferably one or more of citrate, benzoate, tartrate, bromate, iodate, acetate and formates, and specifically preferably, its cation is the same as the soluble phosphate cation in the binder component, and the anion is preferably one or more of acetate ion, formate ion, citrate ion, benzoate ion, tartrate ion, bromate ion and iodate ion, and further specifically, acetate ion or formate ion is preferred, and the anion can also be selected from citrate, benzoate, tartrate, bromate or iodate, but it is required that the solubility of the chemical salt after combining with the cation in water is much greater than the solubility of the soluble phosphate in the raw material. When the tile adhesive powder meets water, the retarder component with higher solubility dissolves in water and undergoes electrolysis, releasing cations identical to soluble phosphates, which increases the cation concentration and inhibits the electrolysis of soluble phosphates after dissolving in water, resulting in a lower concentration of hydrogen phosphate ions in the early solution, thereby achieving the purpose of retarding setting.
[0106] According to the present invention, the mortar composition with hydraulic binder also includes water; the mass of the water is preferably 10% to 20% of the total mass of the other components of the mortar composition with hydraulic binder excluding water, more preferably 12% to 20%, further preferably 14% to 18%, and most preferably 15% to 18%; in some embodiments provided by the present invention, the mass of the water is specifically 15%, 16% or 18% of the total mass of the other components of the mortar composition with hydraulic binder excluding water.
[0107] In a specific embodiment provided by the present invention, the mortar composition comprises a hydraulic binder:
[0108] 25-30 parts by weight of overburned magnesium oxide;
[0109] 8.5-10 parts by weight of soluble phosphate;
[0110] 11.5-15 parts by weight of mineral admixture;
[0111] 30-50 parts by weight of graded sand;
[0112] Redispersible latex powder 0-0.5 parts by weight;
[0113] 0.1 to 0.3 parts by weight of an inorganic temperature regulator;
[0114] Thickener 0.1-1 parts by weight;
[0115] 0.03-0.07 parts by weight of surfactant;
[0116] Thixotropic lubricant 0.1-0.3 parts by weight;
[0117] Retarder; the mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition.
[0118] In another specific embodiment provided by the present invention, the mortar composition comprises a hydraulic binder:
[0119] 25-30 parts by weight of overburned magnesium oxide;
[0120] 8.5-10 parts by weight of soluble phosphate;
[0121] 11.5-15 parts by weight of mineral admixture;
[0122] 40-50 parts by weight of graded sand;
[0123] Redispersible latex powder 0-0.5 parts by weight;
[0124] 0.2 parts by weight of inorganic temperature regulator;
[0125] Thickener 0.18-0.44 parts by weight;
[0126] 0.03-0.07 parts by weight of surfactant;
[0127] 0.2-0.3 parts by weight of thixotropic lubricant;
[0128] Retarder;
[0129] The mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition.
[0130] The present invention uses a gelling system prepared by overburned magnesium oxide, soluble phosphate and a suitable retarder, and adds a tile adhesive mortar prepared by conventional materials, so that the water demand is extremely low and the construction performance is good. In addition, the present invention adopts the dual effects of the retarder and the inorganic temperature regulator, thereby improving the technical problem that the magnesium phosphate gelling system coagulates and hardens too quickly and the tile adhesive is difficult to construct. In addition, polyacrylamide and water-absorbing resin are used as thickeners to solve the problem that the conventional cellulose ether water-retaining agent fails to retain water in the magnesium phosphate gelling system, so that the tile adhesive has a long open time, has the characteristics of fast hardening and early strength, greatly shortens the curing age after pasting tiles, thereby greatly shortening the construction period, can provide subsequent construction work surfaces as soon as possible, and provide more sufficient construction time for subsequent construction operations. At the same time, the adhesive is made dense inside, the hydration product is water-resistant and high-temperature-resistant, can cope with various complex service environments, has a high safety factor for bonding tiles, and the magnesium phosphate gelling system has basically no volume shrinkage and expansion during a long period of time, has good volume stability, and the adhesive hardened body will not shrink and crack during service, thereby improving the safety of tile paving in the later stage.
[0131] The present invention also provides a method for preparing the hydraulic binder for the mortar composition, comprising the following steps: mixing overburned magnesium oxide, soluble phosphate, mineral admixture, graded sand, redispersible latex powder, inorganic temperature regulator, thickener, thixotropic lubricant, retarder and water to obtain the hydraulic binder for the mortar composition.
[0132] The mortar composition provided by the present invention uses raw materials used for the hydraulic binder that are easily available and of stable quality, and is matched with a suitable retarder and conventional materials, has a simple production process, stable finished product quality, and is easy to produce.
[0133] In order to further illustrate the present invention, a hydraulic binder for a mortar composition provided by the present invention and a preparation method thereof are described in detail below in conjunction with embodiments.
[0134] The reagents used in the following examples are all commercially available; the overburned magnesium oxide used in the examples is provided by Huanai Magnesium Industry Co., Ltd. and is obtained by calcining at 1700°C for 6 hours and then sintering and grinding. The powder is brown-yellow and has a specific surface area of 256 m 2 / kg, density is 3.41kg / m 3 The soluble phosphate used in the experiment was mainly purchased from Tianjin Damao Chemical Reagent Factory. The particle size was about 0.2-1mm white particles. The specific surface area of the silica fume used was 18500m 2 / kg; the polyacrylamide used in the test was provided by BASF AG of Germany, which is a cationic polyacrylamide with a molecular weight of 8 to 10 million; the absorbent resin comes from BASF SAVIVAC300 polymer absorbent SAP super absorbent spherical polymer provided by BASF AG of Germany; bentonite comes from sodium bentonite produced by BYK Chemicals of Germany; sepiolite comes from Torsa Group of Spain; metakaolin comes from Shanxi Chaopai Calcined Kaolin Co., Ltd., with a fineness of 1200 mesh and a 28d activity index of 122%; the redispersible latex powder is provided by Wacker Chemical (China) Co., Ltd., which is a vinyl acetate / ethylene copolymer powder; the surfactant comes from Evonik Chemical wetting and leveling agent SURFYNOL 104E, which is an acetylenic diol surfactant containing 50% active ingredients and is a non-ionic gemini surfactant.
[0135] Examples 1 to 3
[0136] The mortar composition was mixed according to the formula in Table 1 to obtain a hydraulic binder.
[0137] Table 1 Formula of hydraulic binder for mortar composition in Examples 1 to 3
[0138]
[0139]
[0140] The setting time of the hydraulic binder of the mortar compositions obtained in Examples 1 to 3 was tested at 20°C according to GB / T 1346-2011. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that under different magnesium phosphate gelling systems, with the addition of appropriate retarder and temperature regulator components, the initial setting time of the mortar composition using a hydraulic binder can be controlled to 30 minutes.
[0141] Example 4 and Comparative Examples 1 to 4
[0142] The mortar composition was mixed according to the formula in Table 2 to obtain a hydraulic binder.
[0143] Table 2 Formula of hydraulic binder for mortar composition in Example 4 and Comparative Examples 1 to 4
[0144]
[0145]
[0146] Figure 3 This is a test chart of the temperature change curve of the hydraulic binder system of the mortar composition in Example 4 and Comparative Examples 1 to 4 using an IP-8 ultrasonic multi-channel tester (the retarding effect of the retarder can be intuitively seen through the temperature change). Figure 3 It can be seen that without adding the retarding component, the exothermic curve of the mortar composition with the hydraulic binder is concentrated after the magnesium phosphate gelling system binder is condensed and mixed with water, the binder hardens very quickly, and the mortar composition with the hydraulic binder has a too short setting time to be difficult to construct. The addition of the retarder causes two temperature change peaks to appear early after the magnesium phosphate gelling system binder is mixed with water. It can also be seen from the temperature curve that the addition of the gelling component delays the reaction time of the system, thereby lengthening the setting time of the magnesium phosphate gelling system to a certain extent, ensuring that the mortar composition with the hydraulic binder mortar has sufficient construction time. Preliminary experiments have found that the first peak intensity and duration will increase the ambient temperature of the magnesium phosphate gelling system binder mortar itself, and have a significant impact on the setting time of the system. The addition of an appropriate amount of retarder and temperature regulator can weaken the first exothermic peak of the magnesium phosphate gelling system binder, and at the same time, the second exothermic peak is earlier than that of the borax and tartaric acid system, thereby ensuring the product operation time while minimizing the negative impact of the retarder on the strength and later performance of the mortar system.
[0147] The setting time of the hydraulic binder of the mortar compositions obtained in Example 4 and Comparative Examples 1-4 was tested at 20°C according to GB / T 1346-2011. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that through Example 4 and Comparative Examples 1, 2, 3 and 4, it is found that the retarder used in the present invention significantly improves the setting time of the magnesium phosphate cementitious system tile adhesive, especially when combined with a temperature regulator of a suitable type and dosage, the effect is more obvious.
[0148] The early compressive strength and bonding strength of the mortar compositions using hydraulic binders in Example 4 and Comparative Examples 1 to 4 were tested according to GB 175-2023 and JC / T 547-2018 standards. Figure 5 .Depend on Figure 5 From the early strength of the binder of the magnesium phosphate gelling system, the early bonding strength and compressive strength of each ratio with the addition of retarder are significantly lower than those of comparative example 1, that is, the ratio without retarding component, but the bonding strength of the formula in Example 4 can still meet 0.6MPa after 6h, and the compressive strength is close to 25.0MPa.
[0149] Examples 5 to 8 and Comparative Examples 5 to 6
[0150] The mortar composition was mixed according to the formula in Table 3 to obtain a hydraulic binder.
[0151] Table 3 Formula of hydraulic binder for mortar composition in Examples 5 to 8 and Comparative Examples 5 to 6
[0152]
[0153] Figure 6The figure is a diagram showing the wetting area of tiles on the concrete slab using the hydraulic binder of the mortar composition obtained in Examples 5 to 8 and Comparative Examples 5 to 6 at different open times, Figure 7 The figure is a comparison of the water retention of the mortar composition obtained in Examples 5 and 7 and Comparative Examples 5 to 6 using a hydraulic binder on a concrete slab. Figure 6 and Figure 7 It can be seen that different types of thickeners have a significant effect on the open time and water retention of magnesium phosphate binder. With the polyacrylamide + water-absorbing resin composite thickener used in the present invention, the magnesium phosphate binder has good wettability for 15 minutes, and the binder loses less water when applied to the concrete board (fewer watermarks seep out around the binder). It is difficult to ensure the water retention of the binder by simply relying on polyacrylamide or water-absorbing resin. Comparative Example 5 has no thickening component, and the binder has a very poor open time and is difficult to construct normally. Comparative Example 6 is a representative of many conventional cellulose ethers (the laboratory tried dozens of cellulose ethers commonly used in mortar for water retention, including but not limited to hydroxyethyl methyl cellulose ether and hydroxypropyl methyl cellulose ether, with a viscosity range of 10000-60000mPas, and the water retention effect of the binder in the magnesium phosphate gelling system is basically similar). Although this series of cellulose ethers has excellent water retention in conventional mortar after addition, the inventor found that the water retention of the binder is not significantly improved under this system.
[0154] Example 9 and Comparative Examples 7-8
[0155] The mortar composition was mixed according to the formula in Table 4 to obtain a hydraulic binder.
[0156] Table 4 Formula of hydraulic binder for mortar composition in Example 9 and Comparative Examples 7-8
[0157]
[0158]
[0159] Figure 8 The early tensile bond strength of the mortar composition obtained in Example 9 and Comparative Examples 7-8 using a hydraulic binder is shown in FIG. Figure 8 It can be seen that the early strength of the fast-hardening and early-strengthening tile adhesive prepared by the present invention develops rapidly. Compared with conventional early-strengthening tile adhesives, the early strength is higher and the fast-hardening and early-strengthening effect is more obvious.
[0160] In summary, the present invention uses a hydraulic binder to prepare a mortar composition with a long operating time and good wettability and construction properties through reasonable mixing of raw materials and matching with other components.
[0161] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A mortar composition using a hydraulic binder, characterized in that: include: Retarder; the mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition; The thickener is selected from polyacrylamide and water-absorbing resin.
2. The mortar composition according to claim 1 is characterized in that: The mass ratio of the polyacrylamide to the water-absorbing resin is 0.2-1:1-4.
3. The mortar composition according to claim 1, characterized in that the hydraulic binder The mineral admixture comprises 5 to 12 parts by weight of heavy calcium powder and 0 to 7 parts by weight of ultrafine filler.
4. The mortar composition according to claim 3 uses a hydraulic binder, characterized in that: The fineness of the heavy calcium powder is 200-400 mesh; The average particle size of the ultrafine filler is 0.2 to 20 μm; The ultrafine filler is selected from one or more of silica fume, metakaolin, granulated blast furnace slag powder, fly ash, limestone powder and heavy calcium powder.
5. The mortar composition according to claim 1 using a hydraulic binder, characterized in that: The graded sand includes 40-70 mesh sand and 70-140 mesh sand; The mass ratio of the 40-70 mesh sand to the 70-140 mesh sand is (0.7-1.2):
1.
6. The mortar composition according to claim 1 using a hydraulic binder, characterized in that: The overburned magnesium oxide is obtained by calcining and grinding magnesite at a high temperature of 1500°C to 1700°C; The overburned magnesium oxide has a mesh size of 250 to 400; The MgO content in the overburned magnesium oxide is 88% to 92%; The soluble phosphate is selected from one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, calcium hydrogen phosphate, disodium hydrogen phosphate and sodium dihydrogen phosphate; The graded sand is selected from one or more of washed sand, machine-made sand, quartz sand and calcium sand; The redispersible latex powder is selected from one or more of vinyl acetate-ethylene copolymer, vinyl acetate-ethylene-vinyl versatate polymer, styrene-acrylate copolymer, vinyl acetate-vinyl versatate-acrylic acid-ethylene copolymer and vinyl chloride-ethylene-vinyl laurate copolymer; The inorganic temperature regulator is selected from one or more of ammonium nitrate, potassium nitrate and ammonium chloride; The surfactant is selected from acetylenic glycol surfactants; The thixotropic lubricant is selected from one or more of inorganic bentonite, attapulgite, and sepiolite; The retarder is selected from one or more of citrate, benzoate, tartrate, bromate, iodate, acetate and formates.
7. The mortar composition according to claim 1 using a hydraulic binder, characterized in that: The mortar composition using the hydraulic binder also includes water; the mass of the water is 10% to 20% of the total mass of other components of the mortar composition using the hydraulic binder except water.
8. The mortar composition according to claim 1 using a hydraulic binder, characterized in that: include: Retarder; the mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition.
9. The mortar composition according to claim 1 using a hydraulic binder, characterized in that: include: Retarder; the mass of the retarder is 2% to 7% of the total mass of the overburned magnesium oxide and the soluble phosphate in the hydraulic binder of the mortar composition.
10. A method for preparing the mortar composition according to claim 1 using a hydraulic binder, characterized in that: The following steps are involved: The overburned magnesium oxide, soluble phosphate, mineral admixture, graded sand, redispersible latex powder, inorganic temperature regulator, thickener, surfactant, thixotropic lubricant and retarder are mixed to obtain a hydraulic binder for a mortar composition.
Citation Information
Patent Citations
Magnesium phosphate cement grout material
CN102643073A
Magnesium phosphate cement based composite material
CN103922694A
Magnesium phosphate cement-based composite material property modifying additive
CN105330197A
Quickly-hardened high-strength ceramic tile adhesive
CN105503106A
Magnesium phosphate grouting material for quick repair and preparation method thereof
CN108069692A